Modellierung der Auswirkungen einer Entkopplung der Direktzahlungen in der EU auf die Flächenallokation und Wiederkäuerproduktion: Eine Analyse unterschiedlicher Modellergebnisse - Balkhausen, Oliver; Banse, Martin; Grethe, Harald; Nolte, Stephan (German Journal of Agricultural Economics, 2005)
Decoupling of direct payments can be expected to have complex effects and the net effect on crop and fodder acreage is unclear. A literature review reveals that various simulation models uniformly project a decline of the cereal and silage maize acreage as well as ruminant production in the EU-15 in the course of decoupling of direct payments. In contrast, model results are mixed with respect to the direction of the decoupling effect on oilseed and pasture as well as voluntary set aside area. The model type is not found to have a systematic effect on model results. It is rather the assumptions about the effects of direct payments on production which differ widely and drive model results to a large extent. A model analysis which is based on the partial agricultural sector model ESIM-2005 highlights the importance of the level of pasture acreage allocation elasticities in the determination of decoupling effects on the distribution of Grandes Cultures and fodder & pasture area.